The imaginary and the process of artistic creation - Corbella, Lucrecia (Linha de Estética do Programa de Pós-Graduação em Filosofia da UFRJ, 2012)
Abstract: This article aims to analyze the notion of imaginary of the philosopher Jean-Paul Sartre and the process of artistic creation of the playwright Luigi Pirandello. From the similarities between The Imaginary, a text by Sartre, and So it is (if it looks), a play by Pirandello, it is possible to conceive the imaginary as a source of artistic creation. The imaginary, for Sartre, as well as being a fundamental determination of a person, is a psychic function that structures the consciousness. What Pirandello does when he writes a play is an invitation, through an imaginary object, to become unreal, distancing themselves from the real world. The art is produced by a enchantment that seeks to invent a world with other meanings enabling new existential choices. Keywords: Sartre; Pirandello; Imaginary; Artistic Creation; Theater.